Ultrasound guidance improves the success rate of axillary plexus block: a meta-analysis - Qin,Qin (2016)
ABSTRACT OBJECTIVE: To evaluate the value of real-time ultrasound (US) guidance for axillary brachial plexus block (AXB) through the success rate and the onset time. METHODS: The meta-analysis was carried out in the Anesthesiology Department of the Second Affiliated Hospital of Soochow University, Suzhou, Jiangsu Province, China. A literature search of Medline, EMBASE, Cochrane database from the years 2004 to 2014 was performed. The literature searches were carried out using medical subject headings and free-text word: "axilla", "axillary", "brachial plexus", "ultrasonography", "ultrasound", "ultrasonics". Two different reviewers carried out the search and evaluated studies independently. RESULTS: Seven randomized controlled trials, one cohort study and three retrospective studies were included. A total of 2042 patients were identified. 1157 patients underwent AXB using US guidance (US group) and the controlled group included 885 patients (246 patients using traditional approach (TRAD) and 639 patients using nerve stimulation (NS)). Our analysis showed that the success rate was higher in the US group compared to the controlled group (90.64% vs. 82.21%, p < 0.00001). The average time to perform the block and the onset of sensory time were shorter in the US group than the controlled group. CONCLUSION: The present study demonstrated that the real-time ultrasound guidance for axillary brachial plexus block improves the success rate and reduce the mean time to onset of anesthesia and the time of block performance.